2021
DOI: 10.48129/kjs.v48i3.9984
|View full text |Cite
|
Sign up to set email alerts
|

The implication of Thorium fraction on neutronic parameters of pebble bed reactor

Abstract: Thorium abundance in the Earth's crust is estimated to be three to four times higher than uranium. This is one potential advantage of Thorium as a provider of attractive fuel to produce nuclear energy. Fewer transuranics produced by Thorium during the fuel burn up in the reactor may also be another advantage for reducing the long-term burden of high-level long-lived waste. The scope of this paper is to study the implication of Thorium fraction on neutronic parameters of pebble bed reactor. The reactor model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…The structural components of the reactor core such as graphite reflectors were easily modeled while the coolant in the reflector side and especially, the reactor shutdown and control systems require special effort in modeling. The modeling and calculations performed in this study were demonstrated successfully in various publications [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Pebbles In Core Modelingmentioning
confidence: 76%
“…The structural components of the reactor core such as graphite reflectors were easily modeled while the coolant in the reflector side and especially, the reactor shutdown and control systems require special effort in modeling. The modeling and calculations performed in this study were demonstrated successfully in various publications [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Pebbles In Core Modelingmentioning
confidence: 76%
“…To obtain these values, a neutronic simulation was performed using the MCNP6.2 radiation transport code with the ENDF/B-VII.0 neutron cross-section library. MCNP is a well-established code for simulating the neutronic aspects of nuclear reactors and has been extensively used for various types of reactors [25][26][27][28][29][30]. Although MCNP may not be the most suitable simulation tool for MSR due to its decoupling from thermal-hydraulic calculations, it has nonetheless been used for simulating various MSR designs, such as MSBR [6,31,32], MSR-FUJI [9], TMSR-500 [33][34][35], and Integral Molten Salt Reactor (IMSR) [36], with good agreement to the reference.…”
Section: Methodsmentioning
confidence: 99%
“…One of the advantages of the Monte Carlo method is to focus on the nuclear uncertainties by reducing the errors related to modeling and design. The critical coefficients (Keff and RTC) for KRITZ-2:13 were calculated by the card KCODE from the code MCNP6.1, which offers complex geometry modeling capabilities with high accuracy 3-D calculations of the physical system [18].…”
Section: Critical Calculationsmentioning
confidence: 99%